Introduction to Nordic cultures - Lindskog, Annika; Stougaard-Nielsen, Jakob (London : UCL Press, 2020)
Introduction to Nordic Cultures is an innovative, interdisciplinary introduction to Nordic history, cultures and societies from medieval times to today. The textbook spans the whole Nordic region, covering historical periods from the Viking Age to modern society, and engages with a range of subjects: from runic inscriptions on iron rings and stone monuments, via eighteenth-century scientists, Ibsen's dramas and turn-of-the-century travel, to twentieth-century health films and the welfare state, nature ideology, Greenlandic literature, Nordic Noir, migration, 'new' Scandinavians, and stereotypes of the Nordic. The chapters provide fundamental knowledge and insights into the history and structures of Nordic societies, while constructing critical analyses around specific case studies that help build an informed picture of how societies grow and of the interplay between history, politics, culture, geography and people. Introduction to Nordic Cultures is a tool for understanding issues related to the Nordic region as a whole, offering the reader engaging and stimulating ways of discovering a variety of cultural expressions, historical developments and local preoccupations. The textbook is a valuable resource for undergraduate students of Scandinavian and Nordic studies, as well as students of European history, culture, literature and linguistics.
Julkaistu myös painettuna.
Kuvailun perustana verkkoaineisto; nimeke PDF-nimiösivulta (OAPEN, katsottu 10.12.2021)
Keywords: Civilization -- Scandinavia; History -- Scandinavia; historia; kulttuuri; kulttuurihistoria; historia; kultur; kulturhistoria; Scandinavia -- Civilization; Scandinavia -- History; Pohjoismaat; Norden